Comandos de produção textual nos anos iniciais do ensino fundamental: aproximações e/ou distanciamentos da proposta curricular (AMOP, 2015) - Bedin, Karime Torres (2023)
In the present research, we focused on the theme "theoretical-analytical study on the textual production commands, elaborated by teachers of Elementary School to guide the practice of student's written production." We started from the principle that commands, when elaborated under the understanding of an interactionist conception of language, and supported by the theoretical-methodological assumptions of the curriculum in question (AMOP, 2015), can be taken as teaching and learning instruments of writing as a form of interaction. In this perspective, we sought to answer the following question: What elements of a proposal of writing as a form of interaction are being guaranteed in written commands of textual production elaborated by teachers of the 4th and 5th grades of Elementary School? Considering this questioning, our general objective was to establish relationships between the theoretical methodological orientations of the curriculum (AMOP, 2015) and the textual production commands elaborated by teachers of the 4th and 5th grades of Elementary School, reflecting on the understanding of textual production that supports them in the direction of this practice. Theoretical-methodologically, we anchored this study in the Dialogic Conception of Language based on the writings of the Bakhtin Circle, more specifically, in the works of Volochinov (2017[1929]) and Bakhtin (2010[1929]), establishing approaches with researchers focused on teaching writing as a form of interaction, such as: Geraldi (1997), Menegassi (2003), Costa Hübes (2012), among others. The investigative process was thus inscribed in the area of Applied Linguistics, supported by the qualitative-interpretative approach, anchored in a documentary analysis research, since, in our study, we qualitatively analyzed 190 commands elaborated and provided by teachers from the Western region of the Paraná state. These commands were divided into three categories: a) commands that contemplate elements of a proposal of writing for interaction; b) commands that partially contemplate them; c) commands that do not contemplate them, distancing themselves from the curricular basis. We found that, after a decade, there was a certain advancement in the elaboration of commands, since teachers guarantee elements that contemplate, even partially, writing as a form of interaction: 46% of the data sent to us contemplate all or at least one of the elements of a proposal of text for interaction. On the other hand, although there is an attempt to dialogue with the theoretical methodological assumptions of the curriculum, the partial result indicates that many teachers seem not to have yet appropriated the interactionist-dialogic conception of language and its implications in proposals of textual production, since 54% of the commands are configured as proposals of writing exercises, which value the teaching of formal language contents, with the predominance of the act of producing text to exercise writing